Predhodno poročilo o raziskovanju minimalnih temperatur v mraziščih pozimi 2004/2005 - Ogrin, Darko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
Temperature conditions in concave relief shapes differ very much from the conditions that are known as typical for Slovenia. Processes of nocturnal cooling in radiative type of weather are more intensive, relief shape enables undisturbed and strong cooling until morning, which results in big temperature differences in relation to area outside the relief shape. Experimental results made in winter 2004/2005, confirmed that when right meteorological conditions are fulfilled, temperatures in such relief shapes are much lower than in areas where absolute minimums measured within the national observing service net.
Keywords: klimatogeografija; microclimate; mikroklima; relief; topography; temperatura; temperaturni obrat; Slovenia; Slovenija